Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1177/1471301217692130
|View full text |Cite
|
Sign up to set email alerts
|

The Role of the Home Environment in Dementia Care and Support: Systematic review of Qualitative Research

Abstract: Background The domestic home is the preferred site for care provision for people with dementia and their families, therefore creating a dementia and caring friendly home environment is crucial. This systematic review synthesised qualitative studies to explore the role of the home environment and identify potential barriers and facilitators in home dementia care and support to inform future practice and research. Methods A systematic search in 12 databases identified international qualitative literature on perc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 36 publications
(42 citation statements)
references
References 69 publications
1
41
0
Order By: Relevance
“…Stakeholders agreed that a person-centred approach prioritising the inherent value of all people with dementia, seeking to uphold rights and promote abilities was important. Professionals often perceived such an approach as being relatively straightforward, while family carers and people living with dementia pointed to a myriad of ethical and practical dilemmas [21,23]. For family carers these dilemmas often linked to the perceived safety of their relative and the family carer's sense of personal responsibility.…”
Section: Main Findingsmentioning
confidence: 99%
See 1 more Smart Citation
“…Stakeholders agreed that a person-centred approach prioritising the inherent value of all people with dementia, seeking to uphold rights and promote abilities was important. Professionals often perceived such an approach as being relatively straightforward, while family carers and people living with dementia pointed to a myriad of ethical and practical dilemmas [21,23]. For family carers these dilemmas often linked to the perceived safety of their relative and the family carer's sense of personal responsibility.…”
Section: Main Findingsmentioning
confidence: 99%
“…For people living with dementia, there can be a tension between independence as an expression of autonomy [20,21] and interdependence enabling people with dementia to remain in their own homes and communities [13]. Qualitative research has explored the ethical dilemmas faced by family carers and professionals in promoting the dignity and autonomy of people living with dementia [21,22] and deciding how best to adapt the home environment to facilitate independence [23]. Less is known about how people living with dementia, family carer and professional perspectives differ.…”
Section: Introductionmentioning
confidence: 99%
“…Although the significance of the physical domestic environment is unquestionable (Gitlin, Liebman, & Winter, 2003;Shaw, 2004;Soilemezi, Drahota, Crossland, & Stores, 2017), its meaning and role remain empirically under-studied. Aminzadeh and colleagues (2010) suggested that home adaptations or restrictions result in disorder or intrusion, and change the emotional meaning of home for people with dementia.…”
Section: Introductionmentioning
confidence: 99%
“…Studies will be critically assessed using the Joanna Briggs Institute’s critical appraisal tool 64. We will follow the data collection process as above, and use QSR NVivo software for data analysis 65…”
Section: Methodsmentioning
confidence: 99%